A low-power consumption metal soft magnetic composite material and preparation method thereof

By diffusing Nd, Dy, and Tb elements at the grain boundary of FeSi-based alloy and forming oxide layers, the problems of high power consumption and easy cladding layer in high-frequency applications are solved, and soft magnetic composite materials with high permeability, low loss and high stability are achieved.

CN114242369BActive Publication Date: 2025-04-11TIANTONG KAILI TECH CO LTD

Patent Information

Application Number
CN202111607751.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-27
Publication Date
2025-04-11
Estimated Expiration
2041-12-27

AI Technical Summary

Technical Problem

The existing metal soft magnetic composite materials consume high power in high-frequency applications, and the insulating coating is prone to fall off or decompose during pressing and annealing, resulting in an increase in hysteresis loss.

Method used

The coating diffusion technology is used to diffuse the low melting point and high resistivity Nd, Dy, and Tb elements to the grain boundary of the FeSi-based alloy, and diffuse to the grain boundary through vacuum heat treatment and form an oxide layer to improve the resistivity and thermal stability of the material.

Benefits of technology

The high permeability and low loss characteristics of metal soft magnetic composite materials are realized, which reduces high-frequency power consumption and improves the stability and production efficiency of the cladding layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure DEST_PATH_IMAGE005
    Figure DEST_PATH_IMAGE005
  • Figure 21459DEST_PATH_IMAGE003
    Figure 21459DEST_PATH_IMAGE003
  • Figure 179405DEST_PATH_IMAGE002
    Figure 179405DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The present invention discloses a low-power metal soft magnetic composite material and a preparation method thereof. The main components of the material are Si and Fe, and the preparation process is ingot casting, coating diffusion, crushing and screening, pressing and forming, and annealing. The advantage is that by coating and diffusing a low-melting point, high-resistivity, and easily oxidizable substance to the FeSi alloy grain boundary, not only the overall resistivity of the material is improved, but also the coating layer is evenly and stably coated on the surface of the grain, tightly combined, not easy to fall off, and can effectively avoid the problem of the insulating layer easily falling off and decomposing and failing in the subsequent pressing and annealing process. Finally, a low-power metal soft magnetic composite material is obtained by this method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-power consumption metal soft magnetic composite material and a preparation method thereof, belonging to the technical field of soft magnetic materials. Background Art

[0002] Metal soft magnetic composite materials not only retain the excellent properties of soft magnetic alloys and ferrites, but also overcome their defects to the greatest extent. They have the advantages of high magnetic permeability, high saturation magnetic density, wide operating frequency, good thermal stability, etc. Since their advent, soft magnetic composite materials have developed rapidly and are widely used in important fields such as energy, information, and national defense. The insulation coating method is the key technology of metal soft magnetic composite materials. At present, the main insulation coating method is to prepare an insulating layer with high resistivity on the surface of metal magnetic powder. Therefore, the materials and processes of insulation coating are the key to the preparation of soft magnetic composite materials, which directly affect the high-frequency performance of the product. After that, the metal magnetic powder core requires greater pressure during the pressing process. The material that is not tightly coated is easy to break and fall off. After pressing, the magnetic core will also produce internal stress and defects, resulting in an increase in hysteresis loss. Therefore, high-temperature annealing is required to eliminate internal stress and reduce hysteresis loss. This requires the coating material to have good high-temperature thermal stability and no thermal decomposition during the annealing process.

[0003] In industrial production, there are three commonly used insulation coating methods: organic coating, inorganic coating and chemical coating. Usually, one or more of these methods are combined. The Chinese invention patent with patent application number 200710156842.6 discloses the use of organic resin to insulate and coat iron-based soft magnetic composite materials. However, during the heat treatment process, the soft magnetic composite material will produce cracks due to the decomposition of the organic resin, which reduces the insulation of the magnetic powder and increases the eddy current loss. The Chinese invention patent with patent application number 201310396266.8 discloses a method for preparing a nanocrystalline soft magnetic composite material. The process uses phosphoric acid passivation and then epoxy resin coating. The high-temperature thermal stability is poor, the annealing temperature is low, and the internal stress generated during the pressing process cannot be effectively removed, resulting in large core loss. In addition, the phosphoric acid waste liquid during the passivation process will cause environmental pollution. The literature Iron-based soft magnetic composites with Mn–Znferritenanoparticles coating obtained by sol–gel method (Source: Journal of Magnetism and Magnetic Materials, 2012, 324(22):3899.) reported a method of coating Mn-Zn ferrite on the surface of metal magnetic powder using sol–gel. Although a good insulating coating layer was obtained, the coating layer was still prone to cracking during the pressing process. In addition, the preparation steps were too complicated and the cost was high, making it difficult to apply in actual production. Therefore, it is urgent to effectively solve the above problems, reduce power consumption while ensuring excellent magnetic properties, and develop new soft magnetic composite materials and their preparation processes suitable for high-frequency applications. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the existing system and preparation method, and to provide a low-power metal soft magnetic composite material and a preparation method thereof. Through reasonable experimental design, an element with extremely low solid solubility, good fluidity and easy oxidation is coated on the FeSi-based alloy, diffused into the grain boundary of the FeSi-based alloy through vacuum heat treatment, and evenly distributed within the grain boundary through fluidity, and then an oxide layer is precipitated at the grain boundary of the soft magnetic alloy through atmosphere heat treatment, thereby increasing the resistivity of the material itself and reducing high-frequency power consumption.

[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:

[0006] The alloy constituting the soft magnetic composite material is based on FeSi, and M elements are diffused into the grain boundaries of the base alloy by coating diffusion. The M metal should be selected from one or more of Nd, Dy and Tb.

[0007] The preparation method of the soft magnetic composite material comprises the following steps:

[0008] (1) putting industrial pure iron and polycrystalline silicon into a vacuum induction furnace according to a composition ratio of Si content of 3wt%-7wt% and the balance of Fe for melting and ingot casting to obtain a FeSi alloy ingot;

[0009] (2) in a glove box, pouring the M metal powder into alcohol, and then adding 0.5wt% of a coupling agent to the alcohol to prepare a suspension, wherein the mass fraction of the M metal powder is 40wt%-60wt%, and coating the suspension onto the FeSi alloy ingot obtained in step (1), and then placing the alloy ingot in a high vacuum sintering furnace for annealing, first heating to 890-920°C, keeping the temperature for 10-16h, then cooling to 450-520°C, keeping the temperature for 4-6h, and finally cooling with the furnace, so that the M metal powder can be fully diffused into the grain boundaries of the alloy ingot;

[0010] (3) mechanically crushing and ball milling the alloy ingot after annealing, and mixing the soft magnetic powder obtained after ball milling according to the classification of -400 mesh, -300 mesh, -200 mesh, and -100 mesh, wherein the mass fraction of the mixed powder is: -100 to +200 mesh accounts for 5-20%, -200 to +300 mesh accounts for 20-30%, -300 to +400 mesh accounts for 30-50%, and the rest is -400 mesh;

[0011] (4) heating the powder to 200-500° C. in an oxygen-containing atmosphere and keeping the temperature for 30-60 min to precipitate an oxide layer at the alloy grain boundary;

[0012] (5) Add binder and lubricant to the heat-treated magnetic powder at 17-19t / cm 2 Pressing under high pressure;

[0013] (6) The pressed soft magnetic composite material is subjected to magnetic field annealing treatment at 500-900° C. for 0.5-3 h, the annealing atmosphere is vacuum, inert gas or reducing gas protection, and the magnetic field strength is 0.01-0.5T.

[0014] In step (2), the oxygen content in the glove box is less than 10 ppm, and the pressure in the high vacuum sintering furnace is less than 1.0×10 -3 Pa, the coupling agent is one or more of a propane coupling agent, a phthalate coupling agent, and an aluminate coupling agent.

[0015] As a preferred embodiment, in step (2), the annealing temperature is 890-920°C, kept at this temperature for 10-16 hours, then cooled to 450-520°C, kept at this temperature for 4-6 hours, and finally cooled in the furnace.

[0016] In step (4), the oxygen-containing atmosphere is a mixed gas of oxygen and an inert gas, wherein the molar content of oxygen is 3%-5%, and the inert gas is argon.

[0017] As a preferred embodiment, in step (4), the mixed powder is heated to 300-400°C in an oxygen-containing atmosphere and kept warm for 30-60 minutes to precipitate an oxide layer at the alloy grain boundary. In step (5), the binder used is one or more of epoxy resin, silicone resin, silicon dioxide, glass powder, boron oxide or water glass, and the amount of the binder is 0.5%-3% of the mass of the soft magnetic powder; the lubricant is one or more of zinc stearate and paraffin powder, and the amount of the lubricant is 0.1%-1% of the mass of the powder.

[0018] In step (6), the inert gas is argon; the reducing gas is hydrogen or a nitrogen-hydrogen mixture;

[0019] As a preferred embodiment, in step (6), magnetic field annealing is performed at 600-800° C. for 0.5-2 h, and the magnetic field intensity is 0.01-0.1 T.

[0020] The binder used in the present invention is one or more of epoxy resin, silicone resin, silicon dioxide, glass powder, boron oxide or water glass, and the amount of the binder used is 0.5%-3% of the mass of the magnetic powder after heat treatment.

[0021] The lubricant used in the present invention is one or more of zinc stearate and paraffin powder, and the amount of the lubricant used is 0.1%-1% of the mass of the magnetic powder after heat treatment.

[0022] The present invention uses a coating diffusion method to diffuse low-melting-point, high-resistivity material into the FeSi alloy grain boundary, thereby improving the overall resistivity of the material and reducing material loss. The atomic radius of the selected diffusion element is 1.5 times the atomic radius of iron and silicon elements, and the solid solubility is extremely low. It will not enter the interior of the iron-silicon crystal to replace the iron and silicon atoms, and can only exist in the grain boundary, which is conducive to diffusion.

[0023] The diffusion elements selected in the present invention have good fluidity and can be evenly distributed in the grain boundaries after diffusion treatment. The low-melting-point elements diffused into the grain boundaries can be evenly and fully coated on the surface of the grains during the heat treatment process and are tightly combined. In addition, the diffusion elements selected in the present invention are easy to oxidize and can form a stable high-resistivity oxide layer at the grain boundaries after atmosphere heat treatment, which can effectively solve the problem that the insulation layer prepared by the current insulation coating process is easy to fall off and decompose and fail in the subsequent pressing and annealing processes.

[0024] The present invention adopts a magnetic field heat treatment process to promote the growth of the magnetic domain of the material, resulting in a reduction in the displacement ratio of the domain wall, making it more difficult for the magnetic domain to rotate, thereby reducing the coercive force and hysteresis loss, thereby obtaining a magnetic powder core with excellent performance.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The preparation process of the present invention makes the coating layer of the metal soft magnetic composite material uniform, tight and stable, avoiding the problem that the insulating layer is easy to fall off and decompose and fail in the subsequent pressing and annealing process, thereby improving production efficiency;

[0027] 2. The metal soft magnetic composite material obtained by the technical solution of the present invention has the characteristics of high magnetic permeability and low loss. The specific technical indicators are: the effective magnetic permeability is higher than 70 at 100kHz and 1V, and the power loss is less than 700kw / m at 50kHz and 100mT. 3 . DETAILED DESCRIPTION

[0028] This embodiment is a preferred implementation manner of the present invention. Based on the embodiment of the present invention, all other embodiments obtained by other technicians without making any creative work belong to the protection scope of the present invention.

[0029] Three groups of samples were used for testing in both the embodiment and the comparative example of the present invention, and the average value was finally taken to compare the electromagnetic performance test data of the embodiment and the comparative example.

[0030] Example 1

[0031] The FeSi alloy ingot was obtained by smelting with 3wt% Si and 97wt% Fe; a suspension containing 40wt% Nd and 0.5wt% coupling agent was added to alcohol to form a suspension, which was coated on the FeSi alloy ingot, and then placed in a high vacuum sintering furnace at a pressure of less than 1.0×10 -3 Pa, annealing was performed at 890°C for 10 hours, then cooled to 450°C for 4 hours, and then cooled with the furnace; the annealed alloy ingots were crushed, ball-milled, screened, particle-sized, and mixed, and the mass fraction of the mixed powder was: -100 to +200 mesh accounted for 5-20%, -200 to +300 mesh accounted for 20-30%, -300 to +400 mesh accounted for 30-50%, and the rest was -400 mesh; the mixed powder was kept at 200°C in an atmosphere with an oxygen content of 3% for 30 minutes, and an oxide layer was precipitated at the grain boundary; epoxy resin and zinc stearate were added to the treated powder, accounting for 1% and 0.1% of the powder mass, respectively, and the mixture was heated to 18 t / cm 2 The molded product was pressed under pressure and kept warm for 0.5 h under a transverse magnetic field at 600 °C in a vacuum condition.

[0032] After testing, the electromagnetic properties of the obtained soft magnetic composite material are shown in the following table:

[0033]

[0034] Example 2

[0035] The FeSi alloy ingot was obtained by smelting with 5wt% Si and 95wt% Fe; a suspension of 50wt% Nd and 0.5wt% coupling agent was added to alcohol and coated on the FeSi alloy ingot, which was then placed in a high vacuum sintering furnace at a pressure of less than 1.0×10 -3 Pa, annealing was performed at 905°C for 13h, then cooled to 480°C for 5h, and then cooled with the furnace; the annealed alloy ingots were crushed, ball-milled, screened, particle-sized, and mixed, and the mass fraction of the mixed powder was -100 to +200 mesh accounting for 5-20%, -200 to +300 mesh accounting for 20-30%, -300 to +400 mesh accounting for 30-50%, and the rest was -400 mesh; the mixed powder was kept at 350°C in an atmosphere with an oxygen content of 4% for 60min, and an oxide layer was precipitated at the grain boundary; epoxy resin and zinc stearate were added to the treated powder, accounting for 3% and 0.6% of the powder mass, respectively, and the mixture was heated to 18t / cm 2 The molded product was pressed under pressure and kept at 700°C in a transverse magnetic field for 1 hour under the protection of a nitrogen atmosphere.

[0036]

[0037] Example 3

[0038] The FeSi alloy ingot was obtained by smelting with 7wt% Si and 93wt% Fe; a suspension of 60wt% Nd and 0.5wt% coupling agent was added to alcohol and coated on the FeSi alloy ingot, which was then placed in a high vacuum sintering furnace at a pressure of less than 1.0×10 -3 Pa, annealing was carried out at 920℃, holding time was 16h, cooling to 510℃ and holding time was 6h, and cooling was carried out with the furnace; the annealed alloy ingot was crushed, ball-milled, screened, particle size proportioned, and mixed, and the mass fraction of the mixed powder was -100~+200 mesh accounting for 5-20%, -200~+300 mesh accounting for 20-30%, -300~+400 mesh accounting for 30-50%, and the rest was -400 mesh; the mixed powder was kept at 500℃, oxygen content of 5% in an atmosphere for 45min, and an oxide layer was precipitated in the grain boundary; water glass and paraffin powder were added to the treated powder, accounting for 2% and 0.5% of the powder mass respectively, and the powder was heated to 19t / cm 2 The molded product was pressed under pressure and kept warm for 2 hours at 800°C in a transverse magnetic field under the protection of a nitrogen-hydrogen mixed atmosphere.

[0039] After testing, the electromagnetic properties of the obtained soft magnetic composite material are shown in the following table:

[0040]

[0041] Comparative Example 1

[0042] 5wt% Si and 95wt% Fe were used for smelting and ingot casting. After crushing, ball milling, screening, particle size matching and mixing, the mass fraction of the mixed powder was: -200~+300 mesh accounted for 20-30%, -300~+400 mesh accounted for 30-50%, and the rest was -400 mesh. Epoxy resin and zinc stearate were added to the mixed powder, accounting for 2% and 0.6% of the powder mass respectively, at 18t / cm 2 The molded product was pressed under pressure and kept at 700°C for 1h under nitrogen atmosphere protection.

[0043] After testing, the electromagnetic properties of the obtained soft magnetic composite material are shown in the following table:

[0044]

[0045] Electromagnetic performance test data of examples and comparative examples

[0046]

Claims

1. A low-power soft magnetic composite material, characterized in that: The preparation steps of the low-power soft magnetic composite material are as follows: (1) Putting industrial pure iron and polysilicon into an induction melting furnace for melting and casting, wherein the Si content is 3wt%-7wt% and the balance is Fe; (2) In a glove box, pour M metal powder into alcohol, then add a coupling agent to the alcohol to prepare a suspension, wherein the M metal is selected from one or more of Nd, Dy, and Tb, and the content of the M metal powder accounts for 40wt%-60wt% of the total mass, and apply the suspension to a FeSi alloy ingot, then place the alloy ingot in a high vacuum sintering furnace for annealing at a temperature of 850-950°C for 10-20h, cool down to 450-550°C, keep warm for 4-8h, and cool with the furnace, so that the M metal powder can fully diffuse into the grain boundaries of the alloy ingot; (3) Mechanically crushing and ball-milling the alloy ingot after annealing, and classifying the obtained soft magnetic powder into -400 mesh, -300 mesh, -200 mesh, and -100 mesh to obtain a mixed powder; (4) heating the mixed powder to 200-500°C in an oxygen-containing atmosphere and keeping the temperature for 10-60 minutes to precipitate an oxide layer at the alloy grain boundary; (5) Add binder and lubricant to the heat-treated magnetic powder at 17-19t / cm 2 Pressing under high pressure; (6) The pressed soft magnetic composite material is subjected to magnetic field annealing treatment at 700-800° C. for 0.5-2 h, the annealing atmosphere is vacuum, inert gas or reducing gas protection, and the magnetic field strength is 0.01-0.1T.

2. The low-power soft magnetic composite material according to claim 1, characterized in that: In step (2), the oxygen content in the glove box is less than 10 ppm, and the gas pressure in the high vacuum sintering furnace is less than 1.0×10 -3 Pa.

3. The low-power soft magnetic composite material according to claim 1, characterized in that: In the step (2), the mass fraction of the coupling agent is 0.5wt%, and the coupling agent is one or more of a propane coupling agent, a phthalate coupling agent, and an aluminate coupling agent.

4. The low-power consumption soft magnetic composite material according to claim 1, characterized in that: In the step (2), the annealing temperature is 890-920°C, the holding time is 10-16h, the temperature is lowered to 450-520°C, the holding time is 4-6h, and the furnace is cooled so that the M metal powder can be fully diffused into the grain boundaries of the alloy ingot.

5. The low-power consumption soft magnetic composite material according to claim 1, characterized in that: In the step (3), the mass fraction of the mixed powder is: -100 to +200 mesh accounts for 5-20%, -200 to +300 mesh accounts for 20-30%, -300 to +400 mesh accounts for 30-50%, and the rest is -400 mesh.

6. The low-power consumption soft magnetic composite material according to claim 1, characterized in that: In the step (4), the mixed powder is heated to 300-400° C. in an oxygen-containing atmosphere and kept at this temperature for 30-60 minutes to precipitate an oxide layer at the alloy grain boundaries.

7. The low-power soft magnetic composite material according to claim 1, characterized in that: In step (4), the oxygen-containing atmosphere is air, or a mixture of oxygen and an inert gas, wherein the inert gas is argon and the molar content of oxygen is 3%-5%.

8. The low-power consumption soft magnetic composite material according to claim 1, characterized in that: In the step (6), magnetic field annealing is performed at 600-800° C. for 0.5-2 h, the magnetic field strength is 0.01-0.1 T, the inert gas is argon, and the reducing gas is hydrogen or a hydrogen-argon mixture.

9. The low-power consumption soft magnetic composite material according to any one of claims 1 to 8, characterized in that: The binder is one or more of epoxy resin, silicone resin, silicon dioxide, glass powder, boron oxide or water glass, and the amount of the binder is 0.5%-3% of the mass of the magnetic powder after heat treatment.

10. The low-power soft magnetic composite material according to any one of claims 1 to 8, characterized in that: The lubricant is one or more of zinc stearate and paraffin powder, and the amount of the lubricant is 0.1%-1% of the mass of the magnetic powder after heat treatment.

Citation Information

Patent Citations

  • Soft-magnetic powder core and method of preparing the same

    CN101226802A

  • One-step heat treatment preparation process method for soft nanocrystalline magnetic powder core

    CN103456480A

  • Manufacturing method of soft magnet silicon-aluminum alloy magnetic powder core with small amounts of rare earth element cerium or lanthanum

    CN101871071A

  • Low-power consumption metal soft magnetic composite material and preparation method thereof

    CN108172358A

Cited By

  • Insulation coating method and application of soft magnetic powder material

    CN121506732A

  • Method for insulating a soft magnetic powder material and use thereof

    CN121506732B